Multicentre pilot randomised clinical trial of early in-bed cycle ergometry with ventilated patients - Michelle E Kho; Alexander J Molloy; France J Clarke; Julie C Reid; Margaret S Herridge; Timothy Karachi; Bram Rochwerg; Alison E Fox-Robichaud; Andrew JE Seely; Sunita Mathur; Vincent Lo; Karen EA Burns; et al. (BMJ Open Respiratory Research)
Introduction Acute rehabilitation in critically ill patients can improve post-intensive care unit (post-ICU) physical function. In-bed cycling early in a patient’s ICU stay is a promising intervention. The objective of this study was to determine the feasibility of recruitment, intervention delivery and retention in a multi centre randomised clinical trial (RCT) of early in-bed cycling with mechanically ventilated (MV) patients.Methods We conducted a pilot RCT conducted in seven Canadian medical-surgical ICUs. We enrolled adults who could ambulate independently before ICU admission, within the first 4 days of invasive MV and first 7 days of ICU admission. Following informed consent, patients underwent concealed randomisation to either 30 min/day of in-bed cycling and routine physiotherapy (Cycling) or routine physiotherapy alone (Routine) for 5 days/week, until ICU discharge. Our feasibility outcome targets included: accrual of 1–2 patients/month/site; >80% cycling protocol delivery; >80% outcomes measured and >80% blinded outcome measures at hospital discharge. We report ascertainment rates for our primary outcome for the main trial (Physical Function ICU Test-scored (PFIT-s) at hospital discharge).Results Between 3/2015 and 6/2016, we randomised 66 patients (36 Cycling, 30 Routine). Our consent rate was 84.6 % (66/78). Patient accrual was (mean (SD)) 1.1 (0.3) patients/month/site. Cycling occurred in 79.3% (146/184) of eligible sessions, with a median (IQR) session duration of 30.5 (30.0, 30.7) min. We recorded 43 (97.7%) PFIT-s scores at hospital discharge and 37 (86.0%) of these assessments were blinded.Discussion Our pilot RCT suggests that a future multicentre RCT of early in-bed cycling for MV patients in the ICU is feasible.Trial registration number NCT02377830.